(untitled) (Superficies y Vacío, 2013)
The influence of nitriding time and applied load in the friction-wear behaviour of an H13 steel has been studied. Weakly ionised plasma unit and a postdischarge plasma reactor were used for nitriding the H13 die steel with variations of nitriding time from 5h to 9h (at 500 ºC). Optical microscopy and microhardness deep profiles of the nitrided layer were obtained for each nitriding time. Standard pin-on-disc wear test were conducted at ambient temperature (18-23 ºC) and dry sliding. It was observed that the higher the nitriding time, the lower the friction coefficient variations and wear rate varied as a function of the applied load. Plastic deformation and abrasion wear resulted to be the main wear mechanism for short sliding distances, while for long sliding distances plastic deformation dominated the wear mechanism and to some extent oxidative wear. The compound layer (white layer) was central for wear and load capacity.